Answer:
y = -6x - 42
Step-by-step explanation:
First solve for y in x = 6 + 6y.
6y + 6 = x
6y = x - 6
6/6y = x/6 - 6/6
y = 1/6x - 1 the slope is 1/6.
Perpendicular lines slopes are negative reciprocals of each other.
So the new equation will have the slope of -6 ( the negative reciprocal of 1/6)
Next solve for "b" by using y = mx + b and the new slope of -6 and the point (-8,6)
y = mx + b
6 = -6(-8) + b
6 = 48 + b
-42 = b
The equation of the line is y = -6x - 42
<u>ANSWER</u>
(0, 1), (1, 3), (2, 9), (3, 27)
<u>EXPLANATION</u>
The first and third options are completely out because the y-value of an exponential function is never zero.
For the second option the y-values has no geometric pattern or common ratio.
For the last option, we can observe the following pattern
![1 = {3}^{0}](https://tex.z-dn.net/?f=1%20%3D%20%20%7B3%7D%5E%7B0%7D%20)
![{3}^{1} = 3](https://tex.z-dn.net/?f=%20%7B3%7D%5E%7B1%7D%20%20%3D%203)
![{3}^{2} = 9](https://tex.z-dn.net/?f=%20%7B3%7D%5E%7B2%7D%20%20%3D%209)
![{3}^{3} = 27](https://tex.z-dn.net/?f=%20%7B3%7D%5E%7B3%7D%20%20%3D%2027)
:
:
![{3}^{x} = y](https://tex.z-dn.net/?f=%20%7B3%7D%5E%7Bx%7D%20%20%3D%20y%20)
The correct choice is the last option
Answer:
5 9/14
Step-by-step explanation:
Answer:
84.80
Step-by-step explanation: 62.72+22.08=84.80